Spark Desensitization of Nanothermites via the Addition of Highly Electro-Conductive Carbon Particles - Pierre Gibot (C, 2022)
In the past decade, the formulation of spark-desensitized nanothermites has considerably advanced, making them safe to handle. When ignited, these materials reveal impressive properties such as high temperatures (>1000 °C), intense heat releases (>kJ/cm3), and sometimes gas generation. Unfortunately, these energetic systems are systematically characterized by an extreme sensitivity to electrostatic discharges, which can cause accidental ignitions during preparation, handling, and transport. The present study examines the electrostatic discharge sensitivity response of an Al/WO3 energetic formulation doped with highly conductive carbon nanoparticles (Ketjenblack EC600JD). The results showed an increased threshold from <0.14 mJ to almost 40 mJ with 18.80 vol. % of KB EC600JD in the energetic mixture. The energetic material was also desensitized to friction stress with a threshold greater than 360 N, in contrast to a value of <4.9 N for an un-doped Al/WO3 energetic composite material. The reactive performance of the system (w/o Ketjenblack additive) was verified in open medium by means of an optical igniter. The heat release was determined by a calorimetric bomb and a decrease of 50% was recorded for the carbon-doped energetic system compared to the pristine Al/WO3 composition.